2016
DOI: 10.1002/zoo.21336
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of mortality in captive pygmy hippopotamus (Choeropsis liberiensis) from 1912 to 2014

Abstract: The pygmy hippopotamus (Choeropsis liberiensis) is an IUCN Red List Endangered species (CITES Appendix II) that has been housed in zoological collections since 1912. As wild populations continue to decline throughout the species' range, successful ex situ breeding and management, including an understanding of morbidity and mortality, are of utmost importance. This study is the first comprehensive review of mortality data from the captive population since 1982 and significantly expands on previous analyses. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
2
9
0
1
Order By: Relevance
“…Figure indicates a high mortality rate for very young animals, especially from birth to 1 year, as previously described by Flacke et al (). One would expect improved survival of zoo‐born neonates and young animals in comparison with wild populations since conditions in captivity remove many of the factors associated with early mortality.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Figure indicates a high mortality rate for very young animals, especially from birth to 1 year, as previously described by Flacke et al (). One would expect improved survival of zoo‐born neonates and young animals in comparison with wild populations since conditions in captivity remove many of the factors associated with early mortality.…”
Section: Discussionsupporting
confidence: 79%
“…Results of the survival by sex analyses further illustrate the discrepancy in first‐year mortality between males and females, an ongoing concern for population management. This discrepancy is due to a higher neonatal (0–30 day) mortality rate for male calves (Flacke et al, ) and has been previously noted as contributing to the female‐skewed sex ratio in the captive population (Zschokke, ). Potential underlying mechanisms for the higher male neonatal mortality rate have not yet been explored.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although a direct comparison should be made with caution, as it is a report from just one institution regarding a different species of bird, it's interesting to note that similarly high chick mortality has been reported in a closely related penguin species. A high rate of neonatal mortality has been described for birds and other classes of animals in captive settings (Flacke, Tkalcic, Steck, Warren, & Martin, 2016; Kohler, Preston, & Lackey, 2006; Leong, Terrell, & Savage, 2004). The underlying reasons for high chick mortality in captivity are not always known, and, in general, the ultimate cause of mortality may not always be clear.…”
Section: Discussionmentioning
confidence: 99%
“…Da Rè et al (2018) found considerable effects on survival in mammals housed in zoological gardens. Moreover, unfavorable environmental conditions usually lead to and relatively high mortality (Flacke et al 2016(Flacke et al , 2017.…”
Section: Introductionmentioning
confidence: 99%